Accuracy of Euler’s gamma expansion without logarithm - Mačys, Juozas Juvencijus; Banys, Rimas (Lietuvos matematikos rinkinys, 2014)
The rational approximations for the Euler–Mascheroni constant using the Euler asymptotic expansion are obtained. The errors of approximations are evaluated. The numerical computations reflect the accuracy of the approximations.